Water Specific MRI T1 Mapping for Evaluating Liver Inflammation Activity Grades in Rats With Methionine‐Choline‐Deficient Diet‐Induced Nonalcoholic Fatty Liver Disease. Issue 5 (25th February 2022) - Wan, Qian; Peng, Hao; Lyu, Jianxun; Liu, Feng; Cheng, Chuanli; Qiao, Yangzi; Deng, Jie; Zheng, Hairong; Wang, Yi; Zou, Chao; Liu, Xin
Abstract : Background: Early detection and grading of liver inflammation are important for the management of nonalcoholic fatty liver disease (NAFLD) patients. There is still lack of a noninvasive way for the inflammation characterization in NAFLD. Purpose: To assess liver inflammation grades by water specific T1 (wT1) in a rat model. Study Type: Prospective. Animal model: A total of 65 male rats with methionine‐choline‐deficient diet‐induced NAFLD and 15 male normal rats as control. Field Strength/Sequence: A 3 T; multiecho variable flip angle gradient echo sequence. Assessment: The wT1 and proton density fat fraction were quantified. Inflammation and fibrosis were assessed histologically with H&E and Sirius red stained slices according to the nonalcoholic steatohepatitis scoring system. Inflammation grade was scored with G0/G1/G2/G3 as none/mild/moderate/severe inflammation in NALFD rats. G0 + G1 and G2 + G3 were combined as none‐to‐mild grade (GL) and moderate‐to‐severe grade (GH) inflammation groups. Statistical Tests: Analysis of variance (ANOVA), Mann–Whitney U test, Spearman's correlation, and receiver operating characteristic (ROC) analysis were performed. The areas under ROC (AUROC) was used for the diagnostic performance of wT1 in discriminating GH and GL. A P value < 0.01 was considered statistically significant. Results: Seventy‐six rats were included in the analysis. The numbers in G0–G3 groups were 5, 16, 13, and 27. wT1 of G0–G3 was 568.55 ± 63.93 msec, 582.53 ± 62.98 msec, 521.21 ± 67.31 msec, and 508.79 ± 60.53 msec. A moderate but significant negative correlation between wT1 and histopathological inflammation grades was observed ( r s = −0.42). The wT1 of GH (512.80 ± 62.22 msec) was significantly lower than GL (579.20 ± 61.89 msec). The AUROC of wT1 was 0.79, and the optimal cut‐off of wT1 was 562.64 msec (sensitivity: 90%, specificity: 76%), for the discrimination of GL and GH. Data Conclusions: wT1 could differentiate none‐to‐mild inflammation from moderate‐to‐severe inflammation in the early stage of the NAFLD rat model. Evidence Level: 1 Technical Efficacy: Stage 1